(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The organizations and institutions of the developed countries have given attention to the subject of the knowledge economy by using advanced technology in the function of tax examination because of the important and effective role in ensuring the accuracy of the tax accounting process procedures, But the General Commission of taxes is still using traditional methods in the field of tax examination which affects the performance of its work. This research aims to explain the level of effect on introducing advanced methods of Economics and knowledge represented by advanced communication technology in the field of practicing tax examination function in the General Commission of taxes, A questionnaire has been used as a means for collecting data from the research sample which is about (62) auditors their responses have been analysed using the percentages and weighted arithmetic mean .The main conclusions of the research that there is extremely effect of knowledge economy through using advanced and effective technology in the General Commission for taxes to develop the function of tax examination.